Digitalizing Learning Materials on Evaluation im Deutschunterricht Course - Primardiana Hermilia Wijayati; Silmy M. Mawardah; Tamara C. Fitrisia (Randwick International of Education and Linguistics Science Journal, 2021)
The purpose of this research and development was to develop learning materials in the form of digital books based on the Flip PDF Professional application to support the Evaluation Im Deutschunterricht course. This development research used the 4D development model of S. Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel, namely (1) Define, (2) Design, (3) Develop, (4) Disseminate. The research subjects were students of the German Language Education study program who took Evaluation Im Deutschunterricht course in 2021. This research used a questionnaire instrument. Descriptive quantitative analysis technique was employed to analyse the questionnaire data from class C students that responses to the digital book and questionnaire data from the validity test of digital book. The content of the book was analysed using Gregory’s content validity theory (2016). The validation results from material expert and media expert indicate that the developed digital book is included in the very high content validity category with a result of 0.96. The results of the implementation to the students indicated that the digital book has an attractive appearance, easy to understand, easy to access, support interaction between lecturers and students, and can improve the learning process. The two results indicated that the digital book for the Evaluation Im Deutschunterricht course is proper to be used on the learning process.